Inclusive Education: The Forms of Violation of Children’s Rights and School Dropouts in the Kadey Division: East Region of Cameroon - Ndjouma Wedjou, Maurice (International Journal of Scientific Research and Management (IJSRM), 2020)
Article 8 of the African Aspirations for 2063 stipulates that the African people are confident that their countries have the ability and competence to realize or accomplish their full potential in development, culture, and peace.  The vast majority of countries in Africa have worked toward establishing flourishing, inclusive, successful and prosperous societies by eradicating any forms of violation of children’s rights (African Union Commission, 2015). Nevertheless, violation of children’s rights remains present in most developing countries including the country of Cameroon. This research aims to explore the forms of violation of children’s rights having a dramatic incident in school attendance in the Kadey Division of Cameroon, East Region of Cameroon. This research work is inductive, values bias and uses the grounded theory of the qualitative method approach. 15 participants have been selected from 3 major focused groups of different stakeholders in the Kadey Division, East Region of Cameroon. The theoretical saturation code was used to explain the relevance of the sample size.   Data were examined using the open, axial, and selective coding processes. The results were tested for internal and external validity based on credibility, dependability, conformability, and transferability consideration. The philosophical focused on subjectivism ontology and interpretivism perspective. The study is an investigative case study model. The study showed that the forms of violation of children’s rights in the Kadey division include the recruitment and use of children, the denial of humanitarian access, the sexual violence against children and the killing and hurting of children. This study encourages school leaders in the Kadey Division to acknowledge that schools are not meant to function apart from the local community. Promoting strong collaborative work ethics between the major educational stakeholders may help prevent and reduce violence against children within and outside the school milieu and therefore duplicate school attendance.  (UNICEF Regional Office for South Asia, 2016).